Evaluasi Sirkularitas Material pada Produk Kertas Daur Ulang menggunakan Material Circularity Indicator (MCI): Studi Kasus UMKM Agroindustri - Syafitri Nazwa Rizqita; Devi Maulida Rahma; Koko Iwan Agus Kurniawan (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2026)
This study evaluates material circularity in recycled paper products within a small-scale agroindustrial system. The increasing volume of paper waste and the dominance of linear production models highlight the need for more efficient material utilization through circular economy approaches. This research aims to quantify the level of material circularity and identify inefficiencies in the production system. A mixed-method approach was employed using an exploratory case study at Palka Kreatif, a small-scale recycled paper enterprise in Yogyakarta, Indonesia. Qualitative data were obtained through direct observation and interviews to map the material flow, while quantitative analysis was conducted using the Material Circularity Indicator to assess resource efficiency based on material input, waste generation, and product utility. The results show that the Material Circularity Indicator value ranges from 0.52 to 0.58, indicating that the system operates in a predominantly circular manner. The high circularity is mainly driven by the use of 100 percent recycled feedstock, eliminating the need for virgin materials. However, the system has not reached optimal circularity due to the presence of unrecovered production residues and the absence of post-consumption material recovery. These findings highlight that improving waste reintegration and establishing a product take-back system are critical to achieving a fully circular production system. This study contributes to the application of material circularity assessment in small-scale agroindustrial systems and supports the development of sustainable production strategies.